Experiencing Music Composition in Middle School General Music - Kaschub, Michele; Smith, Janice P. (Rowman & Littlefield Publishers, 2022)
Experiencing Music Composition in Middle School General Music is designed to help teachers and students create original music through materials and activities that are enticing and accessible. The text offers an innovative approach to composition teaching and learning to promote the development of the compositional capacities of feelingful intention, musical expressivity, and artistic craftsmanship. With instructional materials aligned to real world tasks from the genres of songwriting/choral music, composition and visual media, instrumental music, electronic music and digital media, and music theater, program activities easily fit into existing curricular frames. Students will transition from participation in teacher-facilitated whole class lessons to more independent compositional work using Sketchpages to guide their critical and creative thinking. These unique graphic organizers blend elements of the composer’s notebook with doodle space to help students plan compositions, track their thinking through the compositional process, and document their analysis of completed works.